Effect of Cryogenic Freezing on Food: a Review - S, Kumar (Journal of Postharvest Technology, 2024)
Food materials are perishable by nature. They require processing or preservation techniques to enhance the storage life. Cryogenics is a branch of engineering wherein production of cryogen and the maintenance of low temperature technologies are studied. Such cryogens have a tremendous potential to be used as a total loss refrigerant. Implementing cryogenic solutions in the field of high volume/high-quality food processing is important for a number of reasons. Maintaining proper food temperatures throughout the plant is essential for food preservation and food safety. These are fundamental elements for consistent food quality and the hallmark of top quality. At the same time, high-efficiency cryogenic processes using either carbon dioxide (CO2) or liquid nitrogen (N2) can boost productivity and streamline operations.